What makes public employees want to leave their job? A meta‐analysis of turnover intention predictors among public sector employees. - Hur, Hyunkang; Abner, Gordon (Public Administration Review, 2024)
Despite the growing literature that examines the determinants of turnover intention in the public sector, little effort has been made to systematize the findings from this scholarship. To address this research gap, this study conducts the first meta‐analysis of the literature on turnover intention among public sector employees. The meta‐analysis includes 249 effect sizes from 59 studies concerning the relationship between individual demographic variables, work environment characteristics, job characteristics, HRM practices, work motivation and work attitudes, and factors related to the external environment and turnover intention. It finds that predictors related to public employees' job involvement, job exhaustion, job satisfaction, role ambiguity, affective organizational commitment, and participation in decision making are among the strongest predictors of turnover intention. In contrast, individual demographic predictors show small or negligible effects on turnover intention.